Technology Trust and E-Banking Adoption: The Mediating Effect of Customer Relationship Management Performance - Samsudin, Wahab; Nor Azila, Mohd Noor; Juhary, Ali (2009)
The electronic revolution in the Malaysian banking sector has started in the 1970's. The first visible form of electronic innovation in the Malaysian banking industry was the introduction of Automated Teller Machines in 1981. Finally, on June 1, 2000, the Malaysian Central Bank gave the green light for locally owned commercial banks to offer Internet banking services. Due to the drastic changes in the business environment, it leads financial institutions to revise their marketing strategies to stress long-lasting relationships with customers. Relationships is important criteria in the selection of private bank. In many conditions, customer satisfaction mediates the relationship between antecedent’s factors and marketing performance. Hence, CRM performance is about maintaining good relationship and repurchases behavior, word-of-mouth and customer retention. Trust has been studied in traditional physical commercial environments. In the marketing and management literatures, trust is strongly associated with attitudes toward products, services, and purchasing behaviors. So that, the main objective of this research paper is to investigate the role of CRM performance as the mediator in the relationship between trust and E-Banking adoption. Hence, this empirical paper confirmed the role of customer relationship management performance as the mediators in the relationship between trust and electronic banking adoption.